2004
DOI: 10.1002/ajim.10355
|View full text |Cite
|
Sign up to set email alerts
|

Co‐worker fatalities from hydrogen sulfide

Abstract: Hydrogen sulfide toxicity is uncommon, but potentially deadly. Toxicity is predominantly in new workers and co-worker fatalities occur in a significant minority of cases. Proper training and education on the warning signs of hydrogen sulfide toxicity may help reduce worker fatalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(79 citation statements)
references
References 19 publications
0
74
0
5
Order By: Relevance
“…Job duty analysis showed that 25% of victims were doing repair or maintenance at the time of death [6]. In an additional study of occupational hydrogen sulfide deaths, Hendrickson et al retrospectively reviewed the United States Bureau of Labor Statistics (USBLS) database: the Census of Fatal Occupational Injuries (CFOI) [7]. In this 7 year study from 1993 to 1999, 42 hydrogen sulfide events were recorded, and they resulted in 52 deaths.…”
Section: What Is the Historical And Current Epidemiology Of H 2 S Poimentioning
confidence: 99%
See 4 more Smart Citations
“…Job duty analysis showed that 25% of victims were doing repair or maintenance at the time of death [6]. In an additional study of occupational hydrogen sulfide deaths, Hendrickson et al retrospectively reviewed the United States Bureau of Labor Statistics (USBLS) database: the Census of Fatal Occupational Injuries (CFOI) [7]. In this 7 year study from 1993 to 1999, 42 hydrogen sulfide events were recorded, and they resulted in 52 deaths.…”
Section: What Is the Historical And Current Epidemiology Of H 2 S Poimentioning
confidence: 99%
“…In this 7 year study from 1993 to 1999, 42 hydrogen sulfide events were recorded, and they resulted in 52 deaths. There were 9 multiple victim events and 21% of all fatalities involved co-workers of an index case [7]. Forty-five of these deaths (87%) occurred at the scene [7].…”
Section: What Is the Historical And Current Epidemiology Of H 2 S Poimentioning
confidence: 99%
See 3 more Smart Citations